A review of the contextual issues regarding housing market dynamics in resource boom towns - McKenzie, Fiona Haslam; Brereton, D.; Birdsall-Jones, Christina; Phillips, R.; Rowley, Steven (Australian Housing and Urban Research Institute, 2008)
This positioning paper provides a context for examining housing market dynamics in four Australian resource boom towns: Kalgoorlie and Karratha in Western Australia, and Emerald and Moranbah in Queensland. The impact of the resource boom on housing affordability is examined, as are its effects on a variety of other related socio- economic indicators in those towns, including the availability and appropriateness of housing, community development, social cohesion and exclusion.